High‐Resolution Characterization of Excavation‐Induced Fracture Network Using Continuous and Discrete Inversion Schemes - Mohammadreza Jalali; Ralf Brauchler; Mark Somogyvári; Rémi deLa Vaissière (Water Resources Research)
Abstract The Meuse/Haute‐Marne Underground Research Laboratory provides the location for the experiment designed to investigate the induced fracture network around open or sealed galleries and drifts. The objective of this study is to investigate and reconstruct the hydraulic properties and the geometry of the induced fracture network to improve the insights and validate the conceptual model of the induced fracture network due to the stress redistribution during tunnel excavations. Within the presented study, the cross‐hole responses of the pneumatic tests were analyzed in the first step with an equivalent porous media—3D travel time‐based tomographic approach. In the next step selected 2D profiles of the 3D model domain were inverted using a discrete fracture network inversion approach. The database of the tomographic analysis is based on 18 gas injection tests and 151 pressure interferences, which were recorded between nine closely spaced boreholes. The travel time‐based inversion approach allowed for the reconstruction of the 3D gas diffusivity distribution between nine boreholes with high‐resolution. The applied discrete fracture network inversion approach is based on a transdimensional Markov Chain Monte Carlo (MCMC) methodology and it operates with reversible model updates (jumps) that change the problem dimensions, that is, the number, length and position of fractures within the model domain after each iteration step. The synthesis of the results between the reconstructed 3D diffusivity tomogram and the 2D fracture tomograms improved the insights into the spatial geometry of the induced fracture network around galleries.